Metallic nanoparticle-on-mirror: Multiple-band light harvesting and efficient photocurrent generation under visible light irradiation - Tesler, Alexander; Sannomiya, Takumi; Hejazi, Seyedsina; Mohammadi Eslami, Reza; Vogel, Nicolas; Altomare, Marco; Schmuki, Patrik (Nano Energy, 2021)
We present a photoanode concept for photoelectrochemical (PEC) water splitting based on metal nanoparticles (Au, Ag, Cu) deposited on a Ti mirror (NPoM) to photosensitize an intermediate TiO2 layer to induce the harvesting of light with sub-bandgap photon energies. The generation of hot electron-hole pairs in metallic nanostructures can occur either by intraband excitation, i.e., plasmon electrons, or by the interband transition of the d-band electrons to the unoccupied conduction band states. Our results demonstrate that the underlying Ti mirror significantly amplifies the PEC activity of such NPoM systems in the visible spectral range. We show that the PEC enhancement in the visible spectral range is not limited to the intraband excitations but is affected mainly by the light trapping pathway within the TiO2 layer, i.e. due to a favorable interplay between thin-film interference cavity modes with both intraband and interband excitations. Among tested metals, Cu and Ag NPs demonstrate a 3-fold higher enhancement factor than that of Au NPs, while in both former cases the nature of the excited electrons is different. The experimentally determined internal quantum efficiency demonstrates alternating behavior with wavelength showing higher efficiencies at short wavelengths, which is attributed to the reduced Schottky barrier of the NPoMs at constructive interference maxima.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Fabry-Pérot interference; Interband excitations; Metallic nanoparticles; Photoelectrochemistry; Titanium dioxide; Water splitting